Influence of drilling parameters on temperature and surface roughness of AISI O2 steel - Unal, Engin (Carl Hanser Verlag, 2018)
This study focuses on the machinability of AISI O2 cold work tool steel investigated by using different drilling parameters namely drill bit types, cutting speed and drill feed rate. Cutting temperature and chip formation were used to evaluate the surface roughness. The surface roughness of drilled holes were measured by using a profilometer. The results of the study revealed that the surface roughness was decreased with increasing cutting speed and drill feed rate. HSCo drill bits provided slightly better hole surfaces compared to HSS and HSE type drill bits. Additionally, acceptable chip formations were obtained with HSCo and HSSe drill bits operations. The cutting temperature of the holes was measured using thermocouples. The maximum temperatures were observed with HSS type drill bits, while the minimum temperatures were measured in the group of HSCo drill bits. As a result of this study, it can be evaluated that the HSCo drill bit was the best choice for the optimum drilling performance in machining of AISI O2.
Keywords: AISI O2; HSSCo; surface roughness; chip formation; drilling temperature